Extracutaneous canine sporotrichosis: case report - Siqueira, Leticia Maximiano Bezerra de; Sena, Diana Guiomar Ferreira de; Cardoso, Paula Gabriela da Silva; Santos, Amanda Pina dos; Santos, Edna Michelly de Sá; Ribeiro, Roana Cecília dos Santos (JRG Journal of Academic Studies, 2024)
Sporotrichosis is a subcutaneous mycosis that infects humans and animals, caused by dimorphic fungi of the Sporotrix spp. complex. This article describes a case of extracutaneous canine sporotrichosis in the State of Pernambuco, Brazil, in which the animal presented ulcerated lesions in the nasal mucosa and swelling of the nasal plane, in addition to dyspnea, sneezing and cephalic wiggles. The diagnosis was confirmed after a positive fungal culture, and the animal was treated for six months with oral itraconazole at a dose of 10 mg/kg/SID, with complete remission of the lesions, without adverse effects.